The manifesto as genre in Ibsen’s John Gabriel Borkman - Korte, Christine (Nordlit, 2015)
This article examines John Gabriel Borkman’s neo-aristocratic performance of power and authority in Ibsen’s eponymously titled play (1896). After his downfall, John Gabriel has retreated into his once grand reception hall wherein he has become like a petrified relic from a preceding era. His performance within the “fading glory” of the upstairs hall– a veritable theatre for his delusions of grandeur – is one of an outmoded type of bourgeois “hero” whose flagrantly illicit dealings are no longer tenable as capitalism becomes ever-more “rational” and bureaucratic in its façade. The article focuses on John Gabriel’s performance of a “sovereign” or charismatic authority and examines his future visions as “manifestos”. The manifesto is a form belonging to a feudal era of rule by divine right – one that is necessarily “theatrical” in its performance of a legitimate authority. Assuming the voice of the sovereign, John Gabriel attempts to address the needs of the iron-ore miners – a desiring, albeit latent force in Ibsen’s text. The desires of the workers, however, are continually effaced by the bewitching powers of capitalist abstraction, which account for the alienation of family and individuals in Ibsen’s play. Comparing John Gabriel’s manifesto with Marx and Engels’ Communist Manifesto not only accounts for the end of an age of neo-aristocratic bourgeois decadence, but also marks labour as the definitive socio-political issue of the late 19th century. Where John Gabriel uses a dramaturgy rooted in past models of rule to address the workers in his vision of a benevolent “kingdom”, the Communist Manifesto heralds the death of his class and replaces the voice of the “sovereign authority” with the self-authorising voice of the workers themselves. Borkman’s fatal flaw then is failing to sufficiently address the plight of the iron-ore miners with whom he claims intimate acquaintance but with whom he is grossly out of touch. Ibsen shows us his inevitable failure and the disappearance of the John Gabriel “type” of Romantic industrialist in favour of corrupt lawyers such as Hinkel, who are more adaptable to capitalism’s ever-changing incarnations.